Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

By introducing a gradient-distributed Ca element cladding into the positive electrode material of sodium ion battery, the problem of O3 type material reacting in air is solved, and the stability of the material and battery performance are improved.

CN120511277APending Publication Date: 2025-08-19HUNAN SHANSHAN ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510334708.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

The existing O3-type sodium ion battery positive electrode materials are prone to react with moisture and carbon dioxide in the air, resulting in difficulty in manufacturing the battery, reduced capacity and unstable structure. The existing coating technology may increase internal resistance or be cost-effective.

Method used

The chemical formula of the cathode material of sodium ion battery is NaxNiaFebMncCudZneMfCagOy. The gradient distribution of Ca element mass content gradually decreases from the surface to the center. The distribution of Ca elements in the material is controlled through a suitable sintering process to form a protective layer to isolate the air reaction.

Benefits of technology

It improves the air stability and structural stability of the material, enhances the transmission capacity of sodium ions, improves the cycling and rate performance of the battery, and maintains the discharge specific capacity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120511277A_ABST
    Figure CN120511277A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of sodium-ion battery materials, and discloses a sodium-ion battery positive electrode material, the chemical formula of the sodium-ion battery positive electrode material is NaxNiaFebMncCudZeMfCagOy, and the mass content of Ca element is gradually reduced from the surface of a sodium-ion battery positive electrode material particle to the center of the particle. The preparation method comprises the following steps: mixing and sintering a precursor material, a sodium source and a compound containing an M element to obtain a layered oxide matrix material; and mixing and sintering the layered oxide matrix material and the Ca-containing compound to obtain the sodium-ion battery positive electrode material. The invention also discloses a sodium ion battery. In the sodium-ion battery positive electrode material, the mass content of the Ca element is gradually reduced from the surface of the sodium-ion battery positive electrode material to the center of the particle in a gradient distribution manner, so that the residual alkali on the surface of the material can be reduced, the air stability and the structural stability can be improved and the cycle performance can be finally improved while the capacity of the material is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to sodium ion batteries, and in particular to a sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Sodium-ion batteries, due to their abundant resources, low cost, and excellent safety, have shown great potential for application in areas such as large-scale energy storage and low-speed electric vehicles. Cathode materials are key to the performance of sodium-ion batteries, and O3-type layered oxide cathode materials have attracted considerable attention due to their high specific capacity and ease of industrialization.

[0003] Despite this, O3-type materials still face several challenges in practical application. They have high adsorption capacity and reactivity, and readily react with moisture and carbon dioxide in the air. Furthermore, sodium ions in the crystal lattice tend to spontaneously escape, reacting with adsorbed moisture and carbon dioxide to form alkaline substances. These reactions not only lead to difficulties in the battery manufacturing process, such as slurry gelation and uneven coating density, but can also reduce battery capacity, increase internal resistance, and cause cell expansion during battery cycling and storage.

[0004] To overcome these challenges, researchers have developed a variety of modification strategies to improve the air stability of O3-type materials. Surface coating has proven to be a very effective approach. By forming a protective layer on the surface of the material, the material's contact with air can be effectively blocked or reduced. Common coating materials include metal oxides, acidic substances, and carbon materials. These coatings not only enhance the chemical stability of the material but also improve its electrochemical properties, thereby extending the battery's cycle life and enhancing its overall performance.

[0005] While the above techniques can effectively improve the material's air stability, they can also have some adverse effects. Electrochemically inert oxide coatings can increase the battery's internal resistance, thereby affecting its charge and discharge performance. While carbon coatings offer good electrical conductivity and chemical stability, their relatively high cost may limit their application in large-scale production. Therefore, it is crucial to seek new technologies that can improve the material's air stability and structural stability while maintaining its specific discharge capacity. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a sodium ion battery positive electrode material and a preparation method thereof and a sodium ion battery.

[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is: A sodium ion battery positive electrode material, the chemical formula of the sodium ion battery positive electrode material is Nax Ni a Fe b Mn c Cu d Zn e M f Ca g O y , wherein M is a doping element including one or more of Li, K, Mg, Sr, Ba, B, Al, Ga, Y, Co, V, Zr, Ti, Nb, Mo, W, and Ta, 0.90≤x≤1.05, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.1≤c≤0.6, 0≤d≤0.15, a+b+c+d+e+f+g=1, 0≤e≤0.15, 0≤f≤0.03, 0<g≤0.03, and 1.95<y<2.05; the mass content of the Ca element gradually decreases from the surface of the sodium ion battery positive electrode material particle to the center of the particle.

[0008] The above-mentioned sodium ion battery positive electrode material, preferably, the mass content of Ca element on the surface of the sodium ion battery positive electrode material particle is 0.1~2.0wt%, and the mass content of Ca element on the surface of the sodium ion battery positive electrode material particle is 0.1~1.5wt% higher than the mass content of Ca element in the center of the particle. The mass content of Ca element is the ratio of the mass of Ca element obtained after point scanning of the test point to the mass of all elements on the test point. When the Ca element content on the particle surface is too much and the difference between the Ca element content on the particle surface and the center is too large, the overly thick coating layer will reduce the conductivity of the material and affect the sodium ion transmission. When the surface Ca element content is less and more Ca elements enter the bulk phase, the difference between the Ca element content on the particle surface and the center is too small, the surface protection effect is weak, and the excessive Ca 2+ Squeeze out Na + , which will lead to an increase in residual alkali and a decrease in capacity.

[0009] The above-mentioned sodium ion battery positive electrode material, preferably, the mass content of the Ca element on the surface of the sodium ion battery positive electrode material particles is 0.5~1.0wt%, and the mass content of the Ca element on the surface of the sodium ion battery positive electrode material particles is 0.5~0.8wt% higher than the mass content of the Ca element in the center of the particle.

[0010] The above-mentioned sodium ion battery positive electrode material, preferably, the pH of the sodium ion battery positive electrode material is ≤12.5, the mass percentage of residual Na2CO3 in the sodium ion battery positive electrode material is 0.01%~0.50%, and the mass percentage of NaOH in the sodium ion battery positive electrode material is 0.01%~0.10%.

[0011] As a general inventive concept, the present invention also provides a method for preparing the above-mentioned sodium ion battery positive electrode material, comprising the following steps: (1) Mixing the precursor material, the sodium source and the compound containing the M element and sintering them, cooling them to room temperature, crushing and sieving them to obtain a layered oxide matrix material; (2) The layered oxide matrix material and the compound containing the Ca element are mixed and sintered, and the mixture is cooled to room temperature and then sieved to obtain the sodium ion battery positive electrode material, wherein the sintering is a two-step sintering process, first sintering at 700°C to 850°C for 1 to 3 hours, and then sintering at 500°C to 650°C for 3 to 6 hours.

[0012] In the above preparation method, preferably, in step (1), the sintering temperature is 860°C to 1000°C, and the sintering holding time is 10 to 15 hours.

[0013] In the above preparation method, preferably, in step (1), the sodium source includes one or more of Na2CO3, NaOH, CH3COONa, and Na2C2O4, and the compound containing the element M includes one or more of Li2CO3, K2CO3, MgO, SrCO3, BaO, H3BO3, Al2O3, Ga2O3, Y2O3, Co2O3, V2O5, ZrO2, TiO2, Nb2O5, MoO3, WO3, and Ta2O5.

[0014] In the above preparation method, preferably, in step (2), the compound containing Ca element includes one or more of CaCO3, CaO, and Ca(OH)2.

[0015] In the above preparation method, preferably, in step (2), the mass ratio of the layered oxide matrix material to the Ca element in the compound containing the Ca element is 0.994-0.999:0.001-0.006.

[0016] In the above preparation method, preferably, in step (1) and step (2), the sintering is carried out in compressed air, and the dew point of the compressed air is less than -30°C and the humidity is less than 1%.

[0017] As a general inventive concept, the present invention also provides a sodium ion battery, comprising the above-mentioned sodium ion battery positive electrode material or the sodium ion battery positive electrode material prepared by the above-mentioned preparation method.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) In the sodium ion battery positive electrode material of the present invention, the mass content of the Ca element is distributed in a gradient that gradually decreases from the surface of the sodium ion battery positive electrode material particle to the center of the particle. The Ca element content on the particle surface is 0.1-2.0 wt%, and the difference between the Ca element content on the particle surface and the Ca element content in the particle center is 0.1-1.5 wt%. This avoids the problem of excessively high content of Ca coating layer distributed on the particle surface, which leads to increased material impedance and decreased capacity. Moreover, controlling the appropriate amount of Ca coating on the particle surface can effectively isolate the air and slow down the side reaction with the electrolyte, thereby protecting the material from corrosion. At the same time, the presence of Ca element can effectively capture F - , forming a stable compound, reducing F - The concentration in the electrolyte avoids its reaction with transition metal ions, thereby reducing the dissolution of transition metal elements. The Ca, Ca 2+ Since it contains twice as much Na + positive charge, which helps to increase the interlayer spacing and thus improve the Na + The diffusion capacity of Ca 2+ With O 2- The bonding energy between them is stronger, which helps stabilize the bulk structure of the material and improve its cycle performance. In general, the sodium ion battery positive electrode material of the present invention reduces the residual alkali on the surface of the material while maintaining the material capacity, improves air stability and structural stability, and ultimately improves cycle performance.

[0019] (2) The sodium ion battery positive electrode material of the present invention promotes the decomposition of Ca-containing compounds by selecting a suitable Ca coating amount and adding a short high-temperature platform during the secondary sintering process, and reacts with the residual alkali on the surface of the primary sintering matrix to help sodium melt back; at the same time, short-term high-temperature sintering can promote a small amount of Ca to be doped into the surface layer, while most of it is still coated on the surface, better protecting the surface interface to improve performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 50-cycle curve diagram of the sodium ion positive electrode material in Example 1 of the present invention and Comparative Example 1.

[0021] Figure 2 1 is a SEM cross-sectional view of the sodium ion positive electrode material particle 1 and its detection points in Example 1 of the present invention.

[0022] Figure 3 1 is a SEM cross-sectional view of the sodium ion positive electrode material particle 2 and its detection points in Example 1 of the present invention.

[0023] Figure 4 This is a Ca element distribution diagram obtained by performing EPMA-EDS testing on a slice of the sodium ion positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0024] To facilitate understanding of the present invention, the present invention will be described in more comprehensive and detailed form below in conjunction with the accompanying drawings and preferred embodiments. However, the protection scope of the present invention is not limited to the following specific embodiments.

[0025] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0027] Example 1: A sodium ion battery cathode material of the present invention has a chemical formula of Na 0.992 Ni 0.324 Fe 0.324 Mn 0.334 Ti 0.010 Ca 0.008 The mass content of O2 and Ca elements gradually decreases from the surface of the sodium ion battery positive electrode material particles to the center of the particles.

[0028] The method for preparing the positive electrode material for a sodium ion battery of this embodiment comprises the following steps: (1) Ni 0.33 Fe 0.33 Mn 0.34 The (OH)2 precursor, Na2CO3, and TiO2 were dry-mixed in a molar ratio of 0.99:1.05:0.01 among transition metal, sodium, and titanium. After being mixed evenly, they were heated to 980°C at a heating rate of 3°C / min in a compressed air atmosphere with a dew point of less than -30°C and a humidity of less than 1%. The mixture was sintered for 12 hours, and then cooled to room temperature at a cooling rate of 1°C / min. The mixture was sieved to obtain a layered oxide matrix material Na 1.0 Ni 0.327 Fe 0.327 Mn 0.336 Ti 0.010 O2.

[0029] (2) The layered oxide matrix material and CaCO3 (calculated as the mass of the Ca element) were dry-mixed in a mass ratio of 0.997:0.003. After mixing evenly, the mixture was heated to 750°C at a heating rate of 3°C / min in a compressed air atmosphere with a dew point of less than -30°C and a humidity of less than 1%, sintered for 2 h, then cooled to 600°C at a cooling rate of 1°C / min, sintered for 4 h, and finally cooled to room temperature at a cooling rate of 1°C / min. The mixture was sieved to obtain a sodium ion battery positive electrode material.

[0030] Example 2: A sodium ion battery cathode material of the present invention has a chemical formula of Na 0.992 Ni 0.225 Cu 0.099 Fe 0.324 Mn 0.334 Ti 0.010 Ca 0.008 The mass content of O2 and Ca elements gradually decreases from the surface of the sodium ion battery positive electrode material particles to the center of the particles.

[0031] The method for preparing the positive electrode material for a sodium ion battery of this embodiment comprises the following steps: (1) Ni 0.23 Cu 0.10 Fe 0.33 Mn 0.34 The (OH)2 precursor, Na2CO3, and TiO2 were dry-mixed according to the molar ratio of transition metal, sodium, and titanium of 0.99:1.04:0.01. After being mixed evenly, they were heated to 940°C at a heating rate of 3°C / min in a compressed air atmosphere with a dew point of less than -30°C and a humidity of less than 1%. The mixture was sintered for 12 hours, and then cooled to room temperature at a cooling rate of 1°C / min. The mixture was sieved to obtain the layered oxide matrix material Na 1.0 Ni 0.227 Cu 0.099 Fe 0.327 Mn 0.337 Ti 0.01 O2.

[0032] (2) The layered oxide matrix material and CaCO3 (calculated as Ca element) were dry-mixed in a mass ratio of 0.997:0.003. After being evenly mixed, the mixture was heated to 750°C at a heating rate of 3°C / min in a compressed air atmosphere with a dew point of less than -30°C and a humidity of less than 1%. The mixture was sintered for 2 h, then cooled to 600°C at a cooling rate of 1°C / min, sintered for 4 h, and finally cooled to room temperature at a cooling rate of 1°C / min. The mixture was sieved to obtain a sodium ion battery positive electrode material.

[0033] Example 3: A sodium ion battery cathode material of the present invention has a chemical formula of Na 0.992 Ni 0.243 Zn 0.049 Fe 0.320 Mn 0.360 Cu 0.020 Ca 0.008 The mass content of O2 and Ca elements gradually decreases from the surface of the sodium ion battery positive electrode material particles to the center of the particles.

[0034] The method for preparing the positive electrode material for a sodium ion battery of this embodiment comprises the following steps: (1) Ni 0.25 Zn 0.05 Fe 0.33 Mn 0.37 The (OH)2 precursor, Na2CO3, and CuO were dry-mixed in a ratio of 0.98:1.02:0.02 of transition metal, sodium, and copper. After mixing evenly, the mixture was heated to 950°C at a heating rate of 3°C / min in a compressed air atmosphere with a dew point of less than -30°C and a humidity of less than 1%. The mixture was sintered for 12 hours, and then cooled to room temperature at a cooling rate of 1°C / min. The mixture was sieved to obtain a layered oxide matrix material Na 0.98 Ni 0.245 Zn 0.049 Fe 0.323 Mn 0.363 Cu 0.02 O2.

[0035] (2) The layered oxide matrix material and CaCO3 (calculated as the mass of the Ca element) were dry-mixed in a mass ratio of 0.997:0.003. After mixing evenly, the mixture was heated to 750°C at a heating rate of 3°C / min in a compressed air atmosphere with a dew point of less than -30°C and a humidity of less than 1%, sintered for 2 h, then cooled to 600°C at a cooling rate of 1°C / min, sintered for 4 h, and finally cooled to room temperature at a cooling rate of 1°C / min. The mixture was sieved to obtain a sodium ion battery positive electrode material.

[0036] Example 4: The sodium ion positive electrode material of this embodiment has the chemical formula Na 0.997 Ni 0.326 Fe 0.326 Mn 0.335 Ti 0.010 Ca 0.003 O2; except that in step (2), the mass ratio of the layered oxide matrix material to CaCO3 (calculated as the mass of the Ca element) is 0.999:0.001, the other conditions of the preparation method are the same as those of the preparation method of the positive electrode material in Example 1.

[0037] Example 5: The sodium ion positive electrode material of this embodiment has the chemical formula Na 0.983 Ni 0.322 Fe 0.322 Mn 0.330 Ti 0.010 Ca 0.016 O2; except that in step (2), the mass ratio of the layered oxide matrix material to CaCO3 (calculated as the mass of the Ca element) is 0.994:0.006, the other conditions of the preparation method are consistent with the preparation method of the positive electrode material in Example 1.

[0038] Example 6: The sodium ion positive electrode material of this embodiment has the chemical formula Na 0.992 Ni 0.324 Fe 0.324 Mn 0.334 Ti 0.010 Ca 0.008 O2; except that the sintering system in step (2) is heated to 750°C at a heating rate of 3°C / min, sintered for 6h, and then cooled to room temperature at a cooling rate of 1°C / min, the other conditions of the preparation method are consistent with the preparation method of the positive electrode material in Example 1.

[0039] Example 7: The sodium ion positive electrode material of this embodiment has the chemical formula Na 0.992 Ni 0.324 Fe 0.324 Mn 0.334 Ti 0.010 Ca 0.008 O2; except that the sintering system in step (2) is to heat to 600°C at a heating rate of 3°C / min, sinter for 6h, and then cool to room temperature at a cooling rate of 1°C / min, the other conditions of the preparation method are consistent with the preparation method of the positive electrode material in Example 1.

[0040] Comparative Example 1: The sodium ion battery positive electrode material of this comparative example has the chemical formula Na 1.0 Ni 0.327 Fe 0.327 Mn 0.336 Ti 0.010 O2; except that calcium carbonate is not added in step (2), the other conditions of the preparation method are the same as those of the preparation method of the positive electrode material in Example 1.

[0041] The Ca element content of the sodium ion battery positive electrode materials prepared in Examples 1 to 7 and Comparative Example 1 was tested. The specific test method is: first prepare the sample by FIB slicing, and then analyze the Ca element content by EPMA-EDS point scanning. During the test, two particles were randomly selected, and the test depth was controlled to be the particle surface, 1 / 4 depth from the particle surface, and the particle center. The detection point diagram and Ca element distribution diagram of Example 1 are shown in Figure 2. Figure 2-Figure 4 The Ca contents at different test points of the embodiments and comparative examples are shown in Table 1.

[0042] Table 1 Ca content at different test points of the positive electrode materials for sodium ion batteries in various examples and comparative examples

[0043] The sodium ion battery positive electrode materials prepared in Examples 1 to 7 and Comparative Example 1 were tested for pH and residual sodium content, respectively. The specific method for testing residual sodium is as follows: take 10g of sample and dissolve it in 100mL of glycerol solution, stir for 30min and then filter. Prepare 0.1mol / L HCl solution, place it in an automatic potentiometric titrator, titrate in an equivalence point manner, record the volume of HCl consumed at the jump point, and calculate the residual sodium content of the sample by the above formula, repeat 3 times, and take the test average value. The calculation formula is as follows:

[0044]

[0045]

[0046] Where V1 is the volume of the acid standard solution consumed at the first equivalence point, V2 is the volume of the acid standard solution consumed at the second equivalence point (including the first equivalence point), and V is the volume of the sample, all in mL.

[0047] The above sample was mixed with a conductive agent and a binder in proportion to form a slurry, which was then coated on aluminum foil to prepare a positive electrode. In an argon atmosphere glove box, metallic sodium was used as the negative electrode and glass fiber was used as the separator to assemble a half-cell. The half-cell was charged and discharged twice at 0.1C constant current at room temperature of 25°C and in the voltage range of 2.0-4.0V, and then cycled 50 times at 1C. The test results are shown in Table 2, where the 50-cycle cycle curves of the sodium ion positive electrode materials in Example 1 and Comparative Example 1 are shown in Table 2. Figure 1 shown.

[0048] Table 2 Physical and chemical indicators and electrochemical properties of the positive electrode materials for sodium ion batteries in various examples and comparative examples

[0049] By comparing the test results of Example 1 and Comparative Example 1, it can be seen that Ca coating can effectively improve the air stability of the material and reduce the residual alkali on the surface, while Ca partially entering the bulk phase can stabilize the structure and improve the cycle performance of the material. In addition, due to the large ionic radius of Ca, doping in the Na layer can increase the interlayer spacing and promote the Na + transmission, improving the rate performance of the material. By comparing the test results of Example 1 with Examples 4 and 5, it can be seen that when the added Ca content is low, the Ca coating on the surface is less and the improvement of the material performance is small; when the added Ca content is high, the Ca coating on the surface is thicker, which affects the conductivity of the material and the transmission of sodium ions, thereby affecting the capacity and rate performance. By comparing the test results of Example 1 with those of Example 6 and 7, it can be seen that the coordinated regulation of sintering temperature and sintering time has a significant effect on the distribution of Ca and the performance of the material. Under long-term low-temperature sintering conditions, Ca cannot enter the bulk phase and is retained on the surface, and cannot play a role in enhancing the bulk structure and improving the rate performance. If long-term high-temperature sintering is adopted, although the diffusion ability of Ca is enhanced, excessive bulk doping will occupy the Na site, causing Na to escape and form residual alkali on the surface, while reducing the capacity. The optimized short-term high-temperature sintering process realizes the gradient distribution regulation of Ca by accurately controlling the duration of the high-temperature section, allowing part of Ca to enter the bulk phase to stabilize the structure, and retaining a sufficient amount of Ca to form a coating on the surface, thereby enhancing the protective effect on the surface of the material, and ultimately achieving a balanced optimization of capacity, rate and cycle performance.

[0050] In summary, from the results in Table 1 and Table 2, it can be seen that the best effect can be achieved by selecting the appropriate Ca coating amount and coating sintering system, controlling the surface Ca content to 0.5~1.0wt%, and gradually decreasing the Ca element from the surface to the bulk. When the difference in Ca content between the surface and the center is 0.5~0.8 wt%,

Claims

1. A sodium ion battery cathode material, characterized in that The chemical formula of the sodium ion battery positive electrode material is Na x Ni a Fe b Mn c Cu d Zn e M f Ca g O y , wherein M is a doping element including one or more of Li, K, Mg, Sr, Ba, B, Al, Ga, Y, Co, V, Zr, Ti, Nb, Mo, W, and Ta, 0.90≤x≤1.05, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.1≤c≤0.6, 0≤d≤0.15, 0≤e≤0.15, 0≤f≤0.03, 0<g≤0.03, a+b+c+d+e+f+g=1, 1.95<y<2.05; the mass content of the Ca element gradually decreases from the surface to the center of the sodium ion battery positive electrode material particle.

2. The sodium ion battery positive electrode material according to claim 1, wherein The mass content of Ca element on the surface of the sodium ion battery positive electrode material particle is 0.1-2.0 wt %, and the mass content of Ca element on the surface of the sodium ion battery positive electrode material particle is 0.1-1.5 wt % higher than the mass content of Ca element in the center of the particle.

3. The sodium ion battery positive electrode material according to claim 2, wherein The mass content of Ca element on the surface of the sodium ion battery positive electrode material particle is 0.5-1.0wt%, and the mass content of Ca element on the surface of the sodium ion battery positive electrode material particle is 0.5-0.8wt% higher than the mass content of Ca element in the center of the particle.

4. The sodium ion battery positive electrode material according to claim 1, wherein The pH of the sodium ion battery positive electrode material is ≤12.5, the mass percentage of residual Na2CO3 is 0.01%~0.50%, and the mass percentage of NaOH is 0.01%~0.10%.

5. A method for preparing a positive electrode material for a sodium ion battery according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Mixing the precursor material, the sodium source and the compound containing the M element and sintering them, cooling them to room temperature, crushing and sieving them to obtain a layered oxide matrix material; (2) The layered oxide matrix material and the compound containing the Ca element are mixed and sintered, and the mixture is cooled to room temperature and then sieved to obtain the sodium ion battery positive electrode material, wherein the sintering is a two-step sintering process, first sintering at 700°C to 850°C for 1 to 3 hours, and then sintering at 500°C to 650°C for 3 to 6 hours.

6. The preparation method according to claim 5, wherein In step (1), the sintering temperature is 860°C to 1000°C, and the sintering holding time is 10 to 15 hours.

7. The preparation method according to claim 5, wherein In step (1), the sodium source includes one or more of Na2CO3, NaOH, CH3COONa, and Na2C2O4, and the compound containing the element M includes one or more of Li2CO3, K2CO3, MgO, SrCO3, BaO, H3BO3, Al2O3, Ga2O3, Y2O3, Co2O3, V2O5, ZrO2, TiO2, Nb2O5, MoO3, WO3, and Ta2O5; In step (2), the compound containing Ca element includes one or more of CaCO3, CaO, and Ca(OH)2.

8. The preparation method according to claim 5, wherein In step (2), the mass ratio of the layered oxide matrix material to the Ca element in the compound containing the Ca element is 0.994-0.999:0.001-0.

006.

9. The preparation method according to claim 5, wherein In step (1) and step (2), the sintering is carried out in compressed air, and the dew point of the compressed air is less than -30°C and the humidity is less than 1%.

10. A sodium ion battery, characterized in that: The invention comprises the sodium ion battery positive electrode material according to any one of claims 1 to 4 or the sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Ternary positive electrode material, preparation method thereof and lithium ion battery

    CN112803010A

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN117497728A

  • Positive electrode material of sodium ion battery, preparation method and sodium ion secondary battery

    CN117577827A

  • Gradient doped and coated sodium ion battery layered oxide material and preparation method thereof

    CN118841535A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN118919685A